2019
DOI: 10.1002/adbi.201900022
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐Functionalized Hydrogels Modulate Integrin Expression and Stemness in Adult Human Epidermal Keratinocytes

Abstract: The extracellular matrix (ECM) controls keratinocyte proliferation, migration, and differentiation through β‐integrin signaling. Wound‐healing research requires expanding cells in vitro while maintaining replicative capacity; however, early terminal differentiation under traditional culture conditions limits expansion. Here, a design of experiments approach identifies poly(ethylene glycol)‐based hydrogel formulations with mechanical properties (elastic modulus, E = 20.9 ± 0.56 kPa) and bioactive peptide sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…However, we have previously shown that GL13K does not interfere with early osseointegration in a rabbit model compared to noncoated controls . Responses, or lack thereof, to LamLG3 are likely integrin mediated, as HGFs and OKs have different integrin expression profiles. , An exact, mechanistic understanding of our observed cell selectivity phenomena is one branch of our current work which may enable further peptide-mediated control of keratinocytes . While past work has successfully engineered cell-specific surfaces, , to the best of our knowledge this is first report of a cell-specific, multifunctional peptide coating.…”
Section: Resultsmentioning
confidence: 83%
“…However, we have previously shown that GL13K does not interfere with early osseointegration in a rabbit model compared to noncoated controls . Responses, or lack thereof, to LamLG3 are likely integrin mediated, as HGFs and OKs have different integrin expression profiles. , An exact, mechanistic understanding of our observed cell selectivity phenomena is one branch of our current work which may enable further peptide-mediated control of keratinocytes . While past work has successfully engineered cell-specific surfaces, , to the best of our knowledge this is first report of a cell-specific, multifunctional peptide coating.…”
Section: Resultsmentioning
confidence: 83%
“…Norbornene-functionalized poly(ethylene glycol) was synthesized following established protocols 73 . Briefly, PEG-hydroxyl (PEG-OH; MW 40 kg/mol, 8-arm, hexaglycerol core; JenKemUSA) was combined with a 5× molar ratio of pyridine (Fisher Scientific) and a 0.5× molar ratio of 4-(dimethylamino)pyridine (DMAP; Sigma-Aldrich) with respect to PEG hydroxyls in dichloromethane (DCM; Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Lithium phenyl (2,4,6-trimethylbenzoyl) phosphinate (LAP) photoinitiator was synthesized utilizing established methods 73 . Briefly, equimolar amounts of dimethyl phenylphosphonite (Alfa Aesar) and 2,4,6-trimethylbenzoylphosphonite (Acros Organics) were added to a round-bottom flask and stirred overnight at room temperature under argon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations